For Identity Awareness - Amaghlobeli, Khatuna; Zakaraia, Irma (Advances in Social Sciences Research Journal, 2018)
The article deals with the crucial problem of today’s times – the problem of identity. Our aim is to demonstrate through the views of a Georgian writer, Vazha-Pshavela and a Lebanese-born journalist, Amin Maalouf, who was brought up as a Christian, what determines human identity, and how human sense of belonging – an important aspect of human socialization – evolved throughout XXth century. The research into this issue has demonstrated that both thinkers consider self-knowledge and definition and analysis of one’s identity to be of the highest importance. It can be said that this problem has always been relevant. In the era of globalization, taking into consideration the new existing reality, a new concept of identity needs to be developed, the basis for which will be recognition of not just one, but multiple belongings.